The Sun Is Also A Star - Yoon, Nicola (Delacorte Press, 2016)
#1 New York Times bestselling author Nicola Yoon is back with her second book, and just like Everything, Everything, it's an instant classic with a love story that's just as intense as Maddy and Olly's--get ready for Natasha and Daniel.